Controlled Construction of Cyclic d / l Peptide Nanorods. Issue 2 (5th December 2018) - Silk, Mitchell R.; Mohanty, Biswaranjan; Sampson, Joanne B.; Scanlon, Martin J.; Thompson, Philip E.; Chalmers, David K.
Abstract: Cyclicd  / l peptides (CPs) assemble spontaneously via backbone H‐bonding to form extended nanostructures. These modular materials have great potential as versatile bionanomaterials. However, the useful development of CP nanomaterials requires practical methods to direct and control their assembly. In this work, we present novel, heterogeneous, covalently linked CP tetramers that achieve local control over the CP subunit order and composition through coupling of amino acid side‐chains using copper‐activated azide–alkyne cycloaddition and disulfide bond formation. Cryo‐transmission electron microscopy revealed the formation of highly ordered, fibrous nanostructures, while NMR studies showed that these systems have strong intramolecular H‐bonding in solution. The introduction of inter‐CP tethers is expected to enable the development of complex nanomaterials with controllable chemical properties, facilitating the development of precisely functionalized or "decorated" peptide nanostructures. Abstract : Ordered heterogeneous nanotubes : Covalently linked cyclic peptide tetramers achieve the organized assembly of heterogeneous peptide nanotubes. Cyclic peptide monomers are tethered through amino acid side‐chains using click chemistry and disulfide bond formation and studied by cryo‐TEM, DLS, and NMR.